Characterization of the complete chloroplast genome of black soybeans, Glycine max (L.) Merr. (legume). Issue 2 (3rd July 2019) - Jin, Liang; Wan, Zhiping; Wei, Dan; Yin, Dawei
Abstract: l.Black Soybeans ( Glycine max (L.) Merr.) is a rare legume native for agricultural production by clearing toxins from the body in Chinese medicine. In this study, the chloroplast genome of G. max (L.) Merr. obtained is 151, 212 bp in length as the circular. The overall GC contents of the cp genome are 35.3%. The phylogenetic maximum-likelihood tree was constructed on 18 species the family Leguminosae cp genomes. The result showed that G. max (L.) Merr. is closest related to Glycine soja in genetic evolution relationship. This complete cp genome of Black Soybeans will be important for agriculture in Northeast China